2004
DOI: 10.1111/j.0022-0477.2004.00873.x
|View full text |Cite
|
Sign up to set email alerts
|

An Allee effect at the front of a plant invasion: Spartina in a Pacific estuary

Abstract: Summary1 Spartina alterniflora sets very little viable seed at the leading edges of an invasion in Willapa Bay, Washington, USA, where it was introduced c . 100 years ago. This largely outbreeding, rhizomatous grass recruits into previously unoccupied areas at low density, so young plants initially grow isolated from one another but eventually coalesce to form continuous meadows. 2 Isolated recruits set approximately one-tenth the seed of meadow plants at five sites, spread over the 230 km 2 of Willapa Bay mud… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
111
0
1

Year Published

2004
2004
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 171 publications
(113 citation statements)
references
References 37 publications
(47 reference statements)
1
111
0
1
Order By: Relevance
“…In Section 7, some possible implications of our results in Population Dynamics are given. In particular, our theoretical results are in agreement with the fact that the maximum tolerable depensation can vary with time in the study of fish populations and the observed Allee effect [5] in smooth cordgrass could be modelled with a periodic system such as the one studied here. See [9] for a discussion of some new examples of models exhibiting the Allee effect and, similar to the Beverton-Holt model, having important biological quantities as parameters, for example, intrinsic growth rate, carrying capacity, Allee threshold, and a new parameter, the shock recovery parameter.…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…In Section 7, some possible implications of our results in Population Dynamics are given. In particular, our theoretical results are in agreement with the fact that the maximum tolerable depensation can vary with time in the study of fish populations and the observed Allee effect [5] in smooth cordgrass could be modelled with a periodic system such as the one studied here. See [9] for a discussion of some new examples of models exhibiting the Allee effect and, similar to the Beverton-Holt model, having important biological quantities as parameters, for example, intrinsic growth rate, carrying capacity, Allee threshold, and a new parameter, the shock recovery parameter.…”
Section: Introductionsupporting
confidence: 88%
“…Fewer red sea urchins give rise to worsening feeding conditions of their young and less protection from predation. In some mast flowering trees, such as smooth cordgrass, Spartina alterniflora, a low population density results in lower probability of seed production and germination [5]. In Section 7, some possible implications of our results in Population Dynamics are given.…”
Section: Introductionmentioning
confidence: 96%
“…Grasses have the potential to be similarly invasive in coastal estuaries (e.g. Kuhn & Zedler 1997;Minchinton 2002a,b;Minchinton & Bertness 2003;Davis et al . 2004), but relatively little is known about how they exclude native plants in the intertidal landscape or whether the mechanisms of exclusion are similar to those in terrestrial communities.…”
Section: Introductionmentioning
confidence: 99%
“…1). Isolated colonists set Ͻ1͞10th the seed of plants that have grown vegetatively and coalesced with their neighbors (30), and this has caused a weak Allee effect (29). S. alterniflora spreads within Willapa Bay by seed that floats on the tide, with virtually no recruitment by rhizome fragments (30).…”
mentioning
confidence: 99%
“…This area was colonized about 1985, the plants began coalescing by 2000 (30) and continuous swards of S. alterniflora occupied most of the available substrate at the time of this experiment. To determine relative pollen loads between isolated and meadow plants, we collected stigmas from all experimental plants, as well as additional plants in the Palix River and two other areas within the bay.…”
mentioning
confidence: 99%